CLASSIFICATION OF ACQUIRED LOWER JAW DEFECTS - Kubaev Aziz Saidolimovich (Web of Journals Publishing, 2023)
Optimization of complex prevention, diagnosis, and treatment of patients with inflammatory and oncological diseases of the maxillofacial region, congenital and acquired defects and deformities, and trauma of the maxillofacial region is based on conducting multifaceted comprehensive studies not only in various areas of dentistry but also involving a wide range of related and fundamental disciplines of medicine. This article describes the issues of surgical treatment and rehabilitation of patients with facial and jaw deformities. It should be said that the treatment and rehabilitation of patients with acquired maxillofacial defects is one of the most important medical and social problems of modern dentistry. It is an urgent task to implement adequate and complex rehabilitation measures in the specialized dental care system, because in most cases, OA leads to serious functional and aesthetic disorders that limit the patients' vital activities, make it difficult for them to socialize, and create deep socio-psychological problems. In the article, the author talks about the issues of surgical treatment and rehabilitation of patients with maxillofacial defects by practicing doctors, maxillofacial surgeons, otorhinolaryngologists, and postgraduate residents.
Keywords: lower jaw, surgical treatment of the jaw, mandibular defects.